Organoaluminum cations for carbonyl activation. Issue 97 (20th November 2019) - Kannan, Ramkumar; Chambenahalli, Raju; Kumar, Sandeep; Krishna, Athul; Andrews, Alex P.; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract : A Lewis acidic cationic organoaluminum catalyst is demonstrated to perform aldehyde dimerization and ketone hydrosilylation via a carbonyl activation pathway. Abstract : In search of stable, yet reactive aluminum Lewis acids, we have isolated an organoaluminum cation, [(Me2 NC6 H4 )2 Al(C4 H8 O)2 ] +, coordinated with two labile tetrahydrofuran ligands. Its catalytic performance in aldehyde dimerization reveals turn-over frequencies reaching up to 6000 h −1, exceeding that of the reported main group catalysts. The cation is further demonstrated to catalyze hydroelementation of ketones. Mechanistic investigations reveal that aldehyde dimerization and ketone hydrosilylation occur through carbonyl activation.